The color detection of two cucumber cultivars by NIR Spectroscopy - KUSUMIYATI, KUSUMIYATI; KURNIASARI, INDAH; OKTAVIA, ADE RISTI (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2017)
Kusumiyati, Kurniasari I, Oktavia AR. 2017. The color detection of two cucumber cultivars by NIR Spectroscopy. Asian J Agric 1: 59-65. The color of cucumber fruit can be estimated as fruit quality trait. Genotypes and cultivars affect the color of cucumber fruit. The estimation can be done quickly and without tissue damage by NIR Spectroscopy. The purpose of this study was to determine the accuracy of color quality values with NIR and conventional methods. The experiment was conducted at Horticulture Laboratory, Faculty of Agriculture, Padjadjaran University in 2013. The color components observed were L, a, b, hue and chroma. The results indicated that the predicted component of cucumber color approximates values obtained from conventional methods. Based on the data obtained, the correlation coefficient (r) of color component approaches 1.00 and the standard calibration error (SEC) is low or close to 0.00.